Numerical Analysis Of Static Structure On The Floor Frame Of The Medium Bus - I Gusti Ngurah Bagus, Catrawedarma; Sholeh, Mohamad; Sari, Eli Novita; Wahid, M Abdul; Fiveriati, Anggra (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2024)
In the manufacturing process, the bus frame is one of the essential parts of the vehicle that supports the overall weight of the vehicle, starting from the interior and passengers inside. In this research, we will carry out a structural strength analysis of the frame using the finite element method, which focuses on the floor frame of a medium bus which receives static loading from the bus interior, including seats with the maximum passenger capacity of a medium bus. The numerical analysis uses Solidworks 2021 for the 3D design of floor frames and structural analysis of the strength of medium bus floor frames using static structural toolbar on Ansys Workbench 2018 software by varying ASTM A514, AISI 1020, and Aluminum 2014-T4 materials. The results obtained are numerical analysis using a mesh size of 27 mm. The maximum deformation, maximum equivalent stress Von Mises, and safety factor are the same location for various ASTM A514, AISI 1020, and Aluminum 2014-T4 materials. The lowest deformation of 1.5735 mm occurred when using AISI 1020 material, and the highest deformation was 1.7209 mm when using Aluminum 2024-T4 material. The maximum equivalent stress Von Mises from the front view to section A-A is 101.23 MPa on AISI 1020 material. The safety level of the design with the material is 4.8999. AISI 1020 is the most optimal material for medium bus floor frames with the highest level of safety and lowest deformation.